2011
DOI: 10.1007/s12263-011-0228-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the radioprotective properties of γ-tocotrienol: comparative gene expression profiling in tocol-treated endothelial cells

Abstract: Among the eight naturally occurring vitamin E analogs, c-tocotrienol (GT3) is a particularly potent radioprophylactic agent in vivo. Moreover, GT3 protects endothelial cells from radiation injury not only by virtue of its antioxidant properties but also by inhibition of 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase and by improving the availability of the nitric oxide synthase cofactor tetrahydrobiopterin. Nevertheless, the precise mechanisms underlying the superior radioprotective properties of GT3 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…GT3 protects endothelial cells from radiation-induced injury not only by virtue of its antioxidant properties, but also by inhibition of HMG-CoA reductase and improving the availability of the nitric oxide synthase cofactor tetrahydrobiopterin (44). GT3 induces multiple changes in functional genetic pathways known to be of critical importance in the cellular responses to radiation exposure, such as oxidative stress, DNA damage, cell cycle phase, regulation of cell death, cell proliferation, hematopoiesis and blood vessel development (45). Recently, it has been reported that GT3-mediated protection of intestinal cells occurs via up-regulation of anti-apoptotic and downregulation of pro-apoptotic factors (46).…”
Section: Discussionmentioning
confidence: 99%
“…GT3 protects endothelial cells from radiation-induced injury not only by virtue of its antioxidant properties, but also by inhibition of HMG-CoA reductase and improving the availability of the nitric oxide synthase cofactor tetrahydrobiopterin (44). GT3 induces multiple changes in functional genetic pathways known to be of critical importance in the cellular responses to radiation exposure, such as oxidative stress, DNA damage, cell cycle phase, regulation of cell death, cell proliferation, hematopoiesis and blood vessel development (45). Recently, it has been reported that GT3-mediated protection of intestinal cells occurs via up-regulation of anti-apoptotic and downregulation of pro-apoptotic factors (46).…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, tocotrienols have particular properties that may make them effective against cardiovascular disease. While tocotrienols have antioxidant properties as strong as α-tocopherol (8), they accumulate in endothelial cells to at least 30-fold higher levels than α-tocopherol and modulate at least 20-fold larger numbers of genes in endothelial cells (9, 10). Moreover, γ- and δ-tocotrienols reduce the intracellular levels of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, the rate-limiting enzyme in cholesterol biosynthesis (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…These effects led to enhancement of hematopoietic recovery and improvement of 30-day survival after total body irradiation (TBI) [21-23]. These results suggested that administration of emulsified GT3 by subcutaneous injection has long-term biological effects; however, whether the biological effects are due to the increase of GT3 level in the early phase or the persistent functions as the accumulation in tissues is unknown.…”
Section: Introductionmentioning
confidence: 99%